IMPROVING THE ENTERPRISE SOCIAL POLICY MANAGEMENT SYSTEM - VEDERNIKOV, MYKHAILO; KOSHONKO, OLENA; VOLIANSKA-SAVCHUK, LESIA; ZELENA, MARIA; BAZALIYSKA, NATALIYA; CHERNUSHKINA, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the social policy of the enterprise, its purpose and means. The tools for implementing social policy as components of its mechanism are identified. Factors influencing the formation of the social policy management system of the enterprise are considered. The definitions and main elements of the mechanism of realization of social policy of enterprises are specified. Recommendations for improving the effectiveness of social policy of the enterprise are offered. The structural-logical model of the system of formation, effective provision and increase of the level of social policy of the enterprise is developed. Within the framework of our research, we will focus more on the problems of improving the internal corporate social policy. When examining the incentives and functions of the provision of voluntary social services by an enterprise, many different points of view can be found. On the one hand, it is believed that the traditions that motivate managers to socially protect workers in their enterprises have been inherited from the planned economy. At that time, against the background of insufficient provision of the entire population of the state with a number of material and social benefits, managers tried to provide employees with the necessary level of social protection at the expense of the enterprise. Social policy at the enterprise should be based on the following principles: consideration of material and non-material needs and interests of employees; availability and publicity of the company's expenses; economic feasibility in terms of costs and benefits; absence of duplication of social needs, which are sufficiently satisfied by state or other public institutions; taking into account the growing living standards and value systems of society.
Keywords: social policy; social protection; social expenses; responsibility; personnel management